2011
DOI: 10.1111/j.2040-1124.2011.00163.x
|View full text |Cite
|
Sign up to set email alerts
|

Glucagon‐like peptide‐1 secretion by direct stimulation of L cells with luminal sugar vs non‐nutritive sweetener

Abstract: Aims/Introduction:  Oral ingestion of carbohydrate triggers secretion of glucagon‐like peptide (GLP)‐1, which inhibits the postprandial rise in blood glucose levels. However, the mechanism of carbohydrate‐induced GLP‐1 secretion from enteroendocrine L cells remains unclear. In the present study, GLP‐1 secretion was examined by meal tolerance tests of healthy Japanese volunteers.Materials and Methods:  Twenty‐one healthy Japanese men participated in the study. The meal tolerance test was performed with modified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 37 publications
0
14
0
Order By: Relevance
“…In the ~50 years since the establishment of test solutions containing PHS, knowledge of gastrointestinal carbohydrate absorption and regulation of glucose homeostasis, especially that by incretins, has greatly advanced. We previously reported that inhibition of hydrolysis of disaccharides (sucrose or maltose) by α‐glucosidase inhibitors significantly increased secretion of glucagon‐like peptide‐1 (GLP‐1). In addition, the incretin effect has been reported to be attenuated in prediabetes.…”
Section: Introductionmentioning
confidence: 99%
“…In the ~50 years since the establishment of test solutions containing PHS, knowledge of gastrointestinal carbohydrate absorption and regulation of glucose homeostasis, especially that by incretins, has greatly advanced. We previously reported that inhibition of hydrolysis of disaccharides (sucrose or maltose) by α‐glucosidase inhibitors significantly increased secretion of glucagon‐like peptide‐1 (GLP‐1). In addition, the incretin effect has been reported to be attenuated in prediabetes.…”
Section: Introductionmentioning
confidence: 99%
“…GLP-1-(7-37) is a 31-amino-acid incretin hormone secreted by the endocrine L cells in the gut wall upon glucose intake (6), and the peptide is secreted in response to the nutrient content of the gastrointestinal tract and thus potentiates insulin exocytosis from pancreatic bcells in a glucose-dependent manner (6,7). Additionally, GLP-1 suppresses appetite, glucagon secretion, and gastric emptying, all of which contribute to inhibition of the postprandial rise in plasma glucose concentrations (8). GLP-1 is responsible for up to 60% of the postprandial insulin response (9).…”
Section: Introductionmentioning
confidence: 99%
“…Similar in vitro results indicated that both sugars and artificial sweeteners (e.g. aspartame and sucralose) stimulate and increase the secretion of GLP-1 and GIP (Jang et al, 2007;Ma et al, 2009;Malaisse, 2014;Sakurai et al, 2012). However, the underlying mechanism of sweeteners induced gastrointestinal peptide secretion remains unclear.…”
Section: Physiological Effect Of Sweeteners and Sweet Taste Receptorsmentioning
confidence: 71%
“…Chol-ecystokinin (CCK) and peptide tyrosine-tyrosine (PYY) play a variety of roles in digestive processes, including reduction of food consumption and increasing satiety (Daly et al, 2013;. It has been demonstrated that oral ingestion of glucose and sucrose or directly infusing sugars, including D-isoforms of glucose, galactose and fructose and non-metabolizable analogues of glucose, 3-O-methyl-glucose and a-methyl-glucose, into intestinal lumen can activate with T1R2/T1R3 inducing and increasing GLP-1 and GIP secretion (Dyer et al, 2007;Sakurai et al, 2012;. Brown et al (2012) confirmed that diet soda sweetened with sucralose and acesulfame-K with glucose can increase GLP-1 secretion in healthy subjects.…”
Section: Physiological Effect Of Sweeteners and Sweet Taste Receptorsmentioning
confidence: 99%